Construction of matrix and eMatrix for mobile development methodologies - Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah (IGI Global, 2008)
Mobile computing is getting more and more attention these days, but the fact that there is still inadequate source of development methodologies to support mobile development, triggers the interest in this study to explore issues related to mobile development methodologies.The mobile developers are facing formidable challenges in the development of mobile application due to the specific demand and technical constraints of mobile environment.Selecting a suitable development methodology is believed to be the key answer to all these issues.Thus, this study aimed to propose a solution to resolve the issues.A decision matrix based on Pugh method was constructed to assist mobile developers especially the novices, to choose the methodology that suits the requirements of their mobile development projects.In order to rate the usefulness of the constructed matrix, an electronic version of the matrix was designed and developed, called md-Matrix.Detail descriptions of the processes involved in constructing the matrix and designing the electronic version of the constructed matrix are also described. Analysis of data gathered from a questionnaire given after the test of md-Matrix shows that participants fairly agreed that md-Matrix is useful in helping them to develop a mobile application.